Climate Characteristics of High-Temperature and Muggy Days in the Beijing-Tianjin-Hebei Region in the Recent 30 Years - Guohua Zhang; Jian Guan; Jingyi Ai; Jiangtao Zhang; Xiaoqing Jin (Journal of Electrical and Computer Engineering)
The climate characteristics of high-temperature (37°C and above) and muggy days in the Beijing-Tianjin-Hebei region over the past 30 years from 1981 to 2010 are analyzed. The results are summarized as follows. During this period, the years with the most number of high-temperature days are 1997–2005 and 2009 in the Beijing-Tianjin-Hebei region, while high-temperature extremes appear in 1999, 2000, 2002, 2009, and 2010. This disparity between the years with high-temperature extremes and the years with the most number of high-temperature days is located primarily in the central and southern cities of the Beijing-Tianjin-Hebei region. High-temperature extremes in the southern cities appear in June and July, while high-temperature extremes in the other cities appear in July. The years with the most number of muggy days are 1994, 1997, 1998, 2000, and 2010 in the Beijing-Tianjin-Hebei region, but the years with the extreme muggy conditions appear in 1981, 2002, 2005, and 2010. The most number of muggy days are in July, and the muggy days in July and August account for about 90% of the entire summer. Over the 30-year period, no apparent changes are observed in the number of days with precipitation and the annual precipitation amount.